2020
DOI: 10.1186/s13567-020-00850-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated time-serial transcriptome networks reveal common innate and tissue-specific adaptive immune responses to PRRSV infection

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) infection is the most important viral disease causing severe economic losses in the swine industry. However, mechanisms underlying gene expression control in immunity-responsible tissues at different time points during PRRSV infection are poorly understood. We constructed an integrated gene co-expression network and identified tissue- and time-dependent biological mechanisms of PRRSV infection through bioinformatics analysis using three tissues (lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…CCR5 and CCL4 genes are overexpressed in PRRSV-infected swine compared to in noninfected swine, 7 days post-infection (dpi) [43]. Recently, Lim et al [44] reported that CCL5, with regard to adaptive immune signaling, is upregulated in PRRSV-infected swine at 10 dpi compared to in non-infected swine at 0 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 and CCL4 genes are overexpressed in PRRSV-infected swine compared to in noninfected swine, 7 days post-infection (dpi) [43]. Recently, Lim et al [44] reported that CCL5, with regard to adaptive immune signaling, is upregulated in PRRSV-infected swine at 10 dpi compared to in non-infected swine at 0 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…Multidimensional scaling (MDS) was carried out to demonstrate the closeness among samples per tissue. More detailed methods are previously described by Lim et al [14].…”
Section: Data Processing and Differentially Expressed Gene (Deg) Analysesmentioning
confidence: 99%
“…Correlation-based integration is mainly performed using Pearson and Spearman correlation coefficients, which evaluate linear and ranking relationships; correlation analysis can also be performed using other methods in addition to these two, which provide standard correlation coefficients. To understand the molecular mechanisms using the correlation-based integration method, studies analyzed selected differential expression genesDEGs in the time-series data and others that analyzed the correlation between the transcriptomic and metabolic changes in mice, were studied [91][92][93].…”
Section: Statisticalstatistic-based Integrationmentioning
confidence: 99%